Contributions to the diplomatic activity of the Hungarian Kingdom between 1452 and 1453 - Kanász, Viktor (Verbum – Analecta Neolatina, 2015)
The one and a half decade between the death of Vladislaus I (1444) and Matthias Hunyadi’s ascension to the throne (1458) is one of the most troubled periods in the history of Hungary. The north-western part of the kingdom was controlled by the Bohemian Brethren under the leadership of Jan Jiskra, Frederick III invaded significant amount of lands in Sopron, Vas and Moson counties, and the Ottoman attacks became permanent in the south. Although the kingdom had a legitimately crowned ruler in Ladislaus V, the infant king, living under the guardianship of Frederick III, could not exercise his power. The barons of the country, mainly the homo novus, the governor and voivode of Transylvania, János Hunyadi and the relative of the king, Ulrik Cillei obtained the control over the internal and foreign affairs. Recently, some yet unknown documents surfaced in the State Archives of Milan. Through investigating these letters written between 1452 and 1453, we can refine our historical knowledge of these years, and, in particular, of the diplomatic relations between the Hungarian Kingdom and the towns in Northern Italy.